Absorption of infrared radiation by carbon monoxide at elevated temperatures and pressures: Part A. Advancing the line-by-line procedure based on HITEMP-2010. (October 2017) - Alberti, Michael; Weber, Roman; Mancini, Marco
Highlights: A Line-by-Line procedure has been developed which accurately predicts effective band width (band absorptance) of carbon monoxide using HITEMP-2010. Each absorption line has been truncated to remedy the sub-Lorentzian behavior in the line wings The line-by-line procedure has been used to reproduce all available (published) measured CO-absorption spectra Scrutiny of the high-temperature CO absorption spectra has indicated inconsistency of the measured data CO absorption measurements should be repeated using modern spectroscopy. Abstract: A line-by-line procedure has been developed for calculating the effective band width (band absorptance) of both the fundamental and the first overtone bands of carbon monoxide. The procedure is based on HITEMP-2010 data base and each absorption line has been truncated to remedy the sub-Lorentzian behavior in the line wings. The truncation criterion has been given in the paper. The line-by-line procedure has been used to reproduce all available (published) measured CO-absorption spectra. The calculated effective band width for the fundamental band is within 10% of the measured values while that for the 1 st overtone is within 5% margin for CO pressures as large as 70–80 bar and temperatures not larger than 600 K. For temperatures larger than 600 K and approaching 2700 K, the line-by-line procedure provides the effective band widths that can be as much as 30% lower than those calculated using the measured spectra. The higher the temperature the larger is the difference between the measured and calculated spectra. Scrutiny of the high-temperature CO absorption spectra has indicated inconsistency of the measured data and their inaccuracy in particular at larger wavenumbers. Thus, it is plausible that the accuracy of the line-by-line procedure is better than 30%. For a precise determination of the accuracy, the CO absorption measurements should be repeated using modern spectroscopy.